Monitoring environmental microbiological safety in a frozen fruit and vegetable plant - Cinar, Aycan; Onbaşı, Elif (Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA, 2021)
Ensuring food safety is becoming progressively important in frozen foods due to increased demand and consumption worldwide. The Environmental Monitoring Program (EMP) shall support daily operational activities and monitor the lack of process hygiene & sanitation actions to achieve food safety. The aim of this study was implementation of EMP in the frozen fruit and vegetable factory to identify the place that allows for pathogen/indicator microorganism growth and create preventive actions to reduce or eliminate the risk of cross-contamination. A total of 400 swab samples, Zone 1 (n = 228), Zone 2 (n = 90), Zone 3 (n = 52), Zone 4 (n = 30) were examined for E. coli and Coliform, Total Plate Count (TPC), yeast and mold and environmental Listeria spp. The percentage of satisfying target value before vs after the implementation of EMP was 82% vs. 100% for E. coli, 61% vs. 86% for Coliforms, 48% vs. 77% for TPC and 63% vs. 80% for yeast & mold respectively for Zone 1. Environmental Listeria was not determined in any of the zones. Integration of EMP to food safety management systems is essential to prevent outbreaks, recalls and economic losses. In addition to depending on the developing technologies, EMP should be supported with new corrective actions.
Keywords: Environmental monitoring program (EMP); Food safety; Frozen fruits and vegetables; Pathogen microorganisms (PMO)